PROFIL KETERAMPILAN SOSIAL SISWA SEKOLAH DASAR BERDASARKAN LATAR BELAKANG PENDIDIKAN PRASEKOLAH (TK DAN NON TK) - Saripah, Ipah; Mulyani, Lia (Mimbar Sekolah Dasar, 2015)
The background of this research is importance of mastering social skills by elementary school students, both of which entered formal education (kindergarten) or informal education (family). The research objective is obtaining students' social skills profiles based on preschool educational background (kindergarten and non-kindergarten). The study was conducted in elementary schools Cijerokaso 1 and 2 Bandung using a quantitative approach and descriptive study method. The results have shown: (1) profile of social skills of elementary school students with a kindergarten background in general is at high qualifications and social skills profile of elementary school students with a non kindergarten background in general are at high and medium qualifications; (2) There is no difference in terms of average social skills between elementary school students with kindergarten background and elementary school students with non kindergarten background, either in general or by each category.Keywords: social skills, elementary school student, preschool educational background.